Leading the technology-powered school - Grady, Marilyn L. (Thousand Oaks, Calif. Corwin Press, 2011)
This book offers a cut-to-the-chase approach for busy principals who want to successfully lead with technology for enhanced student learning. Includes strategies for building capacity.
Human capital : the principal as technology leader -- Teachers : the magic link between technology and students -- The technology leadership team -- Core issues. Professional development: the teacher-to-teacher approach -- Cybersafety leadership : guarding the borders -- Assessment : technology use and skills -- Questions and reflections.
Keywords: Educational technology -- United States; Educational leadership -- United States